Prehospital Management Of Obstetric Emergencies: A Paramedic Perspective (The Review of Diabetic Studies, 2025)
Obstetric emergencies pose significant challenges in the prehospital setting, requiring prompt recognition and management by paramedics to optimize maternal and fetal outcomes. This review explores the paramedic's role in managing obstetric emergencies, focusing on epidemiology, clinical assessment, specific interventions, and future directions. Obstetric emergencies contribute substantially to global maternal morbidity and mortality, with higher incidence in low- and middle-income countries. Paramedic training in obstetric emergencies emphasizes systematic assessment, including primary maternal stabilization, recognition of shock, and continuous monitoring. Condition-specific interventions for antepartum, intrapartum, and postpartum emergencies are discussed, such as management of eclampsia, shoulder dystocia, and postpartum hemorrhage. Specialized obstetric equipment and resources in ambulances are highlighted. Effective communication with receiving hospitals and interprofessional collaboration during transport are crucial for optimal outcomes. Challenges include resource constraints in rural areas, variable scope of practice, and cultural considerations. Future directions explore the integration of telemedicine and artificial intelligence-assisted fetal monitoring tools in prehospital obstetric care. The development of enhanced international guidelines for paramedic involvement in maternity care is advocated to promote standardized, evidence-based practice and improve patient safety in obstetric emergencies globally.